The Numerical Evaluation of Hydrate Saturation in Marine Sediment During the Injection Process of Self-Heat Generating Fluid - Kewei Zhang; Kaixiang Shen; Yanjiang Yu; Yingsheng Wang; Jiawei Zhou; Jing Zeng (Journal of Marine Science and Engineering, 2025)
Marine gas hydrates are recognized as a promising offshore energy resource. Self-heat fluid injection is an innovative thermal-enhanced gas recovery technique for hydrate exploitation engineering. This study numerically investigates hydrate saturation during the self-heating reagent injection process in a sub-sea hydrate reservoir, decoupled from gas production interference. This process employs two consecutive stages: reactive chemical flow stage followed by non-reactive flow stage. The simulation output parameters encompass reservoir temperature, fluid saturation, thermal conductivity, and heat flow rate. The base case demonstrates that fluid injection elevates reservoir temperature from 13.0 °C to 29.3 °C and reduces hydrate saturation from 0.40 to 0.21 through coupled heat–mass transfer mechanisms during the reactive flow stage. In the consequent non-reactive flow stage, hydrate saturation decreases to zero. Sensitivity analysis reveals that initial permeability variation governs the hydrate saturation and temperature during the non-reactive phase. The permeability range of less than 15 mD is the optimal threshold preventing hydrate reformation during fluid injection. 55–70 mD permeability triggers severe secondary hydrate generation, which decreases the fluid application feasibility. Fluid flooding demonstrates superior hydrate dissociation efficacy compared to in situ thermal stimulation. This study develops a novel simulation approach to characterize marine hydrate saturation dynamics.